2016
DOI: 10.1016/j.aim.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Operator means of probability measures and generalized Karcher equations

Abstract: Abstract. In this article we consider means of positive bounded linear operators on a Hilbert space. We present a complete theory that provides a framework which extends the theory of the Karcher mean, its approximating matrix power means, and a large part of Kubo-Ando theory to arbitrary many variables, in fact, to the case of probability measures with bounded support on the cone of positive definite operators. This framework characterizes each operator mean extrinsically as unique solutions of generalized Ka… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…for given µ ∈ P ∞ (P), which is the original case of the generalized Karcher equation in [40]. So the properties (i)-(viii) for G, except (iii) and (vii), are known in [40]. Below we will prove (iii) and (vii) for G based on the convergence P r → G as r → 0.…”
Section: 1mentioning
confidence: 91%
See 3 more Smart Citations
“…for given µ ∈ P ∞ (P), which is the original case of the generalized Karcher equation in [40]. So the properties (i)-(viii) for G, except (iii) and (vii), are known in [40]. Below we will prove (iii) and (vii) for G based on the convergence P r → G as r → 0.…”
Section: 1mentioning
confidence: 91%
“…If we write Aτ σ B for the solution X 0 , then τ σ becomes a two-variable operator mean again and the representing function of τ σ is exactly determined by those of τ and σ, see [17]. The restriction to two-variable operator means was also discussed in [40,49] for the generalized Karcher equation mentioned in Remark 3.2.…”
Section: Deformed Operator Meansmentioning
confidence: 99%
See 2 more Smart Citations
“…H. Karcher [3] gave an equational characterization of this mean on Riemannian manifolds, and in [7] Y. Lim and the author showed that this equational characterization could be extended to the cone of positive invertible operators in the C * -algebra of bounded linear maps on a Hilbert space. Later M. Palfia studied more general classes of means and barycenters and more general versions of the Karcher equation [11].…”
Section: Introductionmentioning
confidence: 99%